Penderaan Kanak-Kanak oleh Ibu Bapa atau Penjaga dan Implikasinya Mengikut Undang-Undang Sivil dan Undang-Undang Keluarga Islam di Malaysia: Child Abuse by Parents or Guardian and its Implications According to Civil Law and Islamic Family Law in Malaysia - Noor, Zanariah (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2015)
This article aims to identify jurisdiction governing matters related to the children who are abused by their parents / guardian under civil law (non-shariah law) and Islamic law and the approaches taken by both courts, Civil Courts and Shariah Courts in handling cases related to child abuse. This writing applies content analysis technique. This technique provides insight on how the provisions of child abuse provided in Child Act 2001 and Penal Code and the effects of abuse towards rights of custody and access in Islamic Family Law Enactments are implemented in Malaysia. The child abuse acts are categorised to physical abuse, sexual abuse, emotional abuse and neglecting the child. The perpetrator could be prosecuted under Penal Code for his/her criminal acts. Under Islamic family law, abuse committed by parents or guardian could be used as a factor to end the right of hadānah (custody) and access of the child. The right of hadanah would be passed on to the next in line who is entitle to the right of hadanah.